Interprofessional model on speaking up behaviour in healthcare professionals: a qualitative study. Issue 1 (26th April 2021) - Umoren, Rachel; Kim, Sara; Gray, Megan M; Best, Jennifer A; Robins, Lynne
Abstract : Objectives: Despite training and the recognition that speaking up can mitigate harm to patients and save lives, healthcare professionals do not consistently speak up when they have patient safety concerns. The purpose of this study was to identify barriers to and facilitators of speaking up about patient safety concerns to inform the development of interventions that will increase this behaviour. Design: From October 2017 to February 2018, the study team conducted focus groups and interviews with nurses, advanced practice providers and physicians at three healthcare facilities. Participants were prompted to share their personal experiences with and perspectives on speaking up about patient safety concerns and to discuss strategies for communicating those concerns. Setting: Tertiary academic healthcare centre. Participants: 62 healthcare professionals participated in the study. Purposeful sampling was used to include participants of different health professions and experience levels. Main outcome measures: We planned to answer questions about why more healthcare professionals do not consistently speak up when they have legitimate patient safety concerns and to identify ways to enhance current interventions on speaking up behaviours, Results: Twelve focus group discussions and two interviews were conducted with 62 participants. We identified two recurring themes: (1) The predominantly hierarchical culture of medicine is a barrier to speaking up and (2) Institutional, interpersonal and individual factors can modulate the impact of medicine's hierarchical culture on speaking up behaviours and inform the strategies employed. Conclusions: The data highlighted the importance of moving beyond targeting front-line healthcare professionals for training in the skills of speaking up and engaging institutional leaders and systems to actively promote and reward speaking up behaviours.